2019
DOI: 10.1111/ele.13365
|View full text |Cite
|
Sign up to set email alerts
|

Spatial insurance in multi‐trophic metacommunities

Abstract: Metacommunity theory suggests that dispersal is a key driver of diversity and ecosystem functioning in changing environments. The capacity of dispersal to mitigate effects of environmental change might vary among trophic groups, potentially resulting in changes in trophic interactions and food web structure. In a mesocosm experiment, we compared the compositional response of bacteria, phyto‐ and zooplankton to a factorial manipulation of acidification and dispersal. We found that the buffering capacity of disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
0
23
2
Order By: Relevance
“…Simulation models that included spatial dynamics also accurately represented realistic patterns in focal systems like pitcher-plant communities (Baiser et al, 2013). Dispersal in metacommunities has also been demonstrated, both theoretically and empirically, to provide a sort of "spatial insurance" that buffers communities against perturbations by promoting rescue effects and resource complementarity (Loreau et al, 2003;Limberger et al, 2019), and experiments have confirmed that these same spatial insurance effects can lower the invasibility of local communities when invasive species are the "perturbation" (Howeth, 2017). Intermediate levels of dispersal in a metacommunity also maximize food web linkages and species diversity, the latter of which has been shown to be a deterrent for invaders (Beaury et al, 2020).…”
Section: Metacommunity Perspectivementioning
confidence: 97%
“…Simulation models that included spatial dynamics also accurately represented realistic patterns in focal systems like pitcher-plant communities (Baiser et al, 2013). Dispersal in metacommunities has also been demonstrated, both theoretically and empirically, to provide a sort of "spatial insurance" that buffers communities against perturbations by promoting rescue effects and resource complementarity (Loreau et al, 2003;Limberger et al, 2019), and experiments have confirmed that these same spatial insurance effects can lower the invasibility of local communities when invasive species are the "perturbation" (Howeth, 2017). Intermediate levels of dispersal in a metacommunity also maximize food web linkages and species diversity, the latter of which has been shown to be a deterrent for invaders (Beaury et al, 2020).…”
Section: Metacommunity Perspectivementioning
confidence: 97%
“…Several studies have experimentally controlled connectivity and shown that it affects diversity, EF and stability (France & Duffy 2006;Staddon et al 2010;Haddad et al 2015;Thompson et al 2015;Guelzow et al 2017;Limberger et al 2019). One BEF experiment that explicitly assessed scale while controlling dispersal in a metacommunity.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Evidence is accruing that the manipulation of horizontal and vertical network diversity affects stability and ecosystem function (Srivastava & Bell 2009;Thibaut et al 2012;Fornoff et al 2019;Zhao et al 2019), but few studies have incorporated scale. Experiments have shown that the magnitude and stability of BEF is modified by changes in food web diversity and spatial scale (France & Duffy 2006;Staddon et al 2010;Limberger et al 2019). These studies connected habitat patches via dispersal to study the emergent relationships between B and EF across patches in a metacommunity.…”
Section: Empirical Evidencementioning
confidence: 99%
“…More variable community composition might also decrease the predictability of ecosystem attributes (e.g., ecosystem respiration) at finer scales of ecological organization (McGrady-Steed et al 1997). Conversely, increased variability could also contribute to improved ecosystem function if species migration patterns and recolonization dynamics in disturbed landscapes are consistent with the spatial insurance hypothesis (Loreau et al 2003;Wang and Loreau 2014;Limberger et al 2019). The spatial insurance hypothesis describes an ecological scenario where dispersal among ecosystems in a spatially and temporally variable landscape allows for the coexistence of functionally complementary species.…”
Section: Discussionmentioning
confidence: 99%